The Influence of Organizational Culture and Work-Life Balance on Employee Performance with Job Satisfaction as a Mediating Variable at PT. Bank Maluku Malut Main Branch Ambon - Semuel Souhoka (Westscience Press, 2026)
This study aims to analyze the influence of organizational culture and work-life balance on employee performance with job satisfaction as a mediating variable. The study used a quantitative approach with Partial Least Square (PLS) analysis. The results showed that organizational culture does not directly affect performance, but does affect job satisfaction. Work-life balance affects both job satisfaction and employee performance. In addition, job satisfaction also affects employee performance and is able to mediate the influence of organizational culture and work-life balance on performance. These findings indicate that improving employee performance can be achieved through increasing job satisfaction supported by a good organizational culture and work-life balance.